KRISIS DISIPLIN PENDIDIKAN ISLAM: ANTI PLURALISME - Zainal Lutfi; Hatta Fakhrurrozi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This article discusses the problem of Islamic education from a theological and sociological point of view. The emergence of normative and verbalist Islamic education curriculum distorts the universality of Islam. Islam that is contextual in space and time, always in contact with sociological aspects, should be understood as something that can change its partiality dynamics continuously, even though there is a universal thing that is maintained as a normative belief. On the other hand, the failure of education to produce educational output that is dignified and virtuous has caused some people to distrust the world of education in developing the character and ethics of children. The vote of disbelief is getting stronger with the emergence of the National curriculum model which gives a greater portion of general subjects than religious subjects. This paper is a criticism of the development of the world of education in Indonesia, with the hope that education stakeholders make changes to the education system and the applicable curriculum.